Concurrent Prescription Fills of Opioids and Benzodiazepines Among Postpartum Women During COVID-19 - Amanda J. Abraham, PhD; Shelby R. Steuart, PhD; Emily C. Lawler, PhD; Hailemichael Shone, PhD; Grace Bagwell Adams, PhD (Elsevier, 2024)
Introduction: Concurrent prescribing of opioids and benzodiazepines is associated with increased risk of emergency department visits and overdose. Postpartum women commonly receive opioids for pain after delivery and are at risk for postpartum depression/anxiety. Although prior research finds increases in opioid prescribing and symptoms of depression/anxiety during COVID-19, concurrent prescribing among postpartum women has not been examined in the context of COVID-19. Methods: Using data from a large sample of privately insured postpartum women (N=514,120), the authors compared concurrent prescription fills of opioids and benzodiazepines before March 1, 2020, and after March 1, 2020. Primary outcome variables measured whether a patient ever filled concurrent opioid and benzodiazepine prescriptions and the number of concurrent prescription fills per patient in the 6 months after delivery. Results: Roughly 46.4% of postpartum women filled an opioid prescription, 2.4% filled a benzodiazepine prescription, and 1.2% of women filled a concurrent prescription. Among postpartum women filling a benzodiazepine prescription, 50.7% filled a concurrent opioid prescription. The number of concurrent fills among postpartum women significantly increased during the early period of COVID-19. On average, postpartum women filled 0.009 more concurrent prescriptions than expected on the basis of the preexisting trend, representing a 22.0% increase in the number of concurrent prescriptions relative to the sample mean. Conclusions: Concurrent prescribing of opioids and benzodiazepines places postpartum women at higher risk of emergency department visits and overdose. To reduce the harms associated with concurrent prescribing, clinicians should carefully consider whether opioids and/or benzodiazepines are clinically necessary for treatment and consult their state prescription drug monitoring program prior to prescribing these medications.